2015
DOI: 10.12659/msm.894249
|View full text |Cite
|
Sign up to set email alerts
|

Admission Glucose and Risk of Early Death in Non-Diabetic Patients with ST-Segment Elevation Myocardial Infarction: A Meta-Analysis

Abstract: BackgroundImpaired admission glucose (AG) is considered to significantly increase risk on both early and late death of the patients with ST-segment elevation myocardial infarction (STEMI), especially for non-diabetic patients; however, some reports contradict the relationship. We therefore conducted a meta-analysis to clarify this issue.Material/MethodsPubMed, EMBASE, Web of Science, and Cochrane Library databases were systematically searched to identify all related prospective cohort studies. The relative ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The association of increased blood glucose with short-term mortality has been well established. [ 1 , 2 ] The high blood glucose level is often observed in CAD patients with an acute event owing to stress response. [ 35 ] It is reported that 25% of AMI patients had newly diagnosed DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of increased blood glucose with short-term mortality has been well established. [ 1 , 2 ] The high blood glucose level is often observed in CAD patients with an acute event owing to stress response. [ 35 ] It is reported that 25% of AMI patients had newly diagnosed DM.…”
Section: Discussionmentioning
confidence: 99%
“…Acute glycemic disorder, indicated by a high plasma glucose level, is a powerful predictor of prognosis in patients with acute myocardial infarction (AMI) but without diabetes mellitus (DM). [ 1 , 2 ] Increased glucose level may suggest previously undiagnosed DM [ 3 ] ; however, the glycemic test is rarely used to diagnose diabetes in patients encountering AMI because the glucose level could increase at the acute phase of cardiac events in all patients. [ 4 , 5 ] Glycated hemoglobin (HbA1c), reflecting the average blood glucose level of the past 2 to 3 months, is a well-known biomarker of long-term glycometabolic control [ 6 ] and is also recommended in the diagnosis of DM since 2010.…”
Section: Introductionmentioning
confidence: 99%
“… 37 For example, a meta-analysis including six cohort studies reported that elevated admission glucose (≥6.1–11.1 mmol/L) was significantly associated with short-term mortality in patients with STEMI without diabetes (RR 4.38; 95% CI 3.23 to 5.94). 38 In another study conducted in patients with NSTEMI undergoing PCI, admission blood glucose was a predictor of 30-day major adverse cardiovascular events (MACE), irrespective of diabetes status. 36 Our results suggested that admission glucose might be a predictor of short-term mortality and in-hospital complications in patients with STEMI aged 65–84 years old, while in patients with NSTEMI it was associated with in-hospital complications only.…”
Section: Discussionmentioning
confidence: 99%